SISTEM INFORMASI ANGGARAN DAN REALISASI DANA BANTUAN OPERASIONAL SEKOLAH DENGAN VISUAL BASIC 60 STUDI KASUS DID SMK AL MBTADI-IN CANDI MULYO - Munadiroh Munadiroh; Tantik Sumarlin (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
In connection with the rapid development of information technology and the increasing ability of computers to help solve problems in the business world, a computerized system in the era of globalization is needed by various parties. Technology that is growing rapidly now is very supportive for a school’s information system, especially with the use of computer-based technology or better known as the Computer Based Information System, with the use of computers in an information system will more quickly save labor and costs. Likewise, Smk Al Mubtadi-in Mulyo Temple relies heavily on a well-computerized system. With the problems obtained from this research, a system is designed to make a report that is integrated quickly, precisely and accurately. The writing method used is in accordance with the RnD (Research And Development) method. Used from writing this thesis, to testing the final product to product implementation. In the management of school operational assistance funds. In making information programs use the Microsoft Visual Basic 6.0 and MySQL (* .sql) programming languages ​​for application design.